METAFORA KONSEPTUAL PADA LIRIK LAGU SOUNDTRACK ANIME “FULLMETAL ALCHEMIST: BROTHERHOOD”: KAJIAN SEMANTIK KOGNITIF - Fauzan, Muhammad; Aibonotika, Arza; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study discusses about the song lyrics that containt conceptual metaphore from soundtrack of animation called “Fullmetal Alchemist: Brotherhood”. Every singer has a variety of language style of their song lyrics to make it more interesting to hear, like metaphore. In this study, we will discuss about the song lyrics that containt conceptual metaphore from soundtrack of animation called “Fullmetal Alchemist: Brotherhood”. The data from this study is the song lyrics from anime soundtrack “Fullmetal Alchemist: Brotherhood” that has conceptual metaphore. The method used in this study is a qualitative descriptive method. The source of data from this research is 10 types of songs from soundtrack of animation called “Fullmetal Alchemist: Brotherhood”. There is 4 types of conceptual metaphore found in anime soundtrack of “Fullmetal Alchemist: Brotherhood”, its structural metaphore, orientasional metaphore, ontological metahpore and personification ontologikal metaphore. Every conceptual metaphor also have their source domain which is the metaphore it self, and target domain as a meaning of the source domain. The results of the analysis of conceptual metahpore that reveal a few types of meaning, like leksical meaning, and conceptual meaning. There also reveal a few types image schemas from the mentioned conceptual metaphor, like force schemas, identity schemas, existence schemas, containtment schemas, and space schemas. Every conceptual meaning has a connection to their image schemas, for example space image schemas have a conceptual meaning like, „emptiness‟, „increasing‟, and „closeness‟.Key Words: Conceptual metaphore, Song lyric, Fullmetal Alchemist: Brotherhood